Implementasi Program Makassar Recover Sebagai Model Penanganan Pandemi Covid 19 Di Kota Makassar - Muhammad Ramli (Jurnal Administrasi Publik dan Pemerintahan, 2026)
Makassar City as the government center of South Sulawesi must be a model in handling covid-19 effectively and efficiently.This study aims to analyze the effec-tiveness of handling covid-19 in Makassar City through the Makassar Recover program,  what strategies the government has taken to revive the com-munity's economy which became the covid 19 pandemic and the constraints and challenges. The results showed that the Makassar Recover program was considered effective in overcoming COVID-19 in Makassar City. The effectiveness of this program includes policies that are right on target and right implementation. The main target of the Makassar Recover Program is suspected COVID-19 patients. Based on the questionnaires distributed, the data ob-tained that 54% are right on target. The synergy between the government and the community in encouraging the fulfillment of the Makassar recovery program target in handling COVID-19 is also very high at 39%. In the Makassar Recover program, known as the Detector Task Force, which functions to filter and monitor the door to door method of residents' homes, the Raika Task Force which works to parse and targets business places, entertainment and events, and the last is the Covid Hunter Task Force which works with suspected Covid-19 cases. carry out tracing, testing and treatment. Various efforts have been prepared by the government to encourage economic strengthening in the midst of the Covid 19 pandemic. The targets are business actors, especially MSMEs. By developing a digital-based marketing concept, presenting a tourist aisle and economic hybridization.